Geodiversity hotspots in Itabirito. - Leite, Frederico Arthur Souza (2023)
Objectives: The objective of this work is to establish the Geodiversity Index for the municipality of Itabirito. It is expected to identify Geodiversity Hotspots, priority areas for conservation. Theoretical Framework: The literature review addressed geological resources, geodiversity and geoconservation of the Iron Quadrangle. Currently, the relevance of geodiversity is growing among scientific journals, research groups and government programs. Method: As a methodology, based on a bibliographical review of scientific works to determine the Geodiversity Index, and collection of secondary data on the physical environment of Itabirito, a grid polygon was created in the QGIS software, measuring 250x250m. To define the degree of influence of each of the variables considered, the Analytic Hierarchy Process method was used. Next, maps were created for each of the six variables as well as for the Geodiversity Index. Results and conclusion: The result of the Analytic Hierarchy Process method obtained a consistency rate of 3.7% to determine the weights of each adopted variable. Then the equation can be established to determine the Itabirito Geodiversity Index. Implications of the research: Exactly in areas that presented high to very high IGD, geodiversity hotspots can be determined. The mapping and analyzes carried out confirm that the municipality of Itabirito has regions considered Geodiversity Hotspots. Originality/Value: This work contributes significantly to the knowledge of the geodiversity of the municipality of Itabirito. The establishment of the IGD for the Itabirito territory is relevant to guide the creation of mechanisms to promote geoconservation and geotourism.